FRG3, a Target of slmiR482e-3p, Provides Resistance against the Fungal Pathogen Fusarium oxysporum in Tomato - Ji, Hui-Min; Zhao, Min; Gao, Ying; Cao, Xin-Xin; Mao, Hui-Ying; Zhou, Yi; Fan, Wen-Yu; Borkovich, Katherine A.; Ouyang, Shou-Qiang; Liu, Peng (Frontiers in Plant Science, 2018)
The vast majority of plant disease resistance (R) genes encode nucleotide binding site–leucine-rich repeat (NBS-LRR) proteins, which specifically determine the plant immune response and have been demonstrated to be targets of several microRNA (miRNA) families. The fungus Fusarium oxysporum f. sp. lycopersici (FOL) causes vascular wilt disease in tomato worldwide. Here, we explored a possible role for FGR3 in tomato defense against FOL. FRG3 is a predicted NBS-LRR like gene that is targeted by slmiR482e-3p, a member of slmiR482 miRNA family. Northern blot data demonstrated that all seven members of the slmiR482 family were regulated in diverse ways after infection by FOL. The ability of FRG3 to be regulated by slmiR482e-3p was confirmed at the transcript level by co-expression studies in in Nicotiana benthamiana. A virus-induced gene silencing (VIGS) approach revealed that FRG3 confers resistance to the Motelle tomato cultivar. Taken together, our study has identified a novel R gene, FRG3, which is targeted by slmiR482e-3p at the transcript level, and is necessary for resistance to tomato wilt disease in planta.